2019
DOI: 10.1016/j.jtho.2019.08.1515
|View full text |Cite
|
Sign up to set email alerts
|

P2.04-10 Biomarkers of Pathological Response on Neo-Adjuvant Chemo-Immunotherapy Treatment for Resectable Stage IIIA NSCLC Patients

Abstract: hepatitis. They also contributed to all-grade hypothyroidism, hyperthyroidism and pneumonitis. These toxicities have significant impact on patients' quality of life, ultimately affecting patients' compliance. A timely intervention with proper supportive care is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Peripheral densities of activated CD4 + T cells (CD69 + ) and NK cells (CD107a + ) were reduced post neoadjuvant therapy in patients who achieved pCR in resected tumors (78). Also, the authors found a decrease in the expression of PD-1 on peripheral CD4 + , CD8 + , and NK cells post neoadjuvant chemo-immunotherapy in patients who achieved pCR in resected tumors (78). Investigation of peripheral immunophenotyping in larger patient cohorts and across trials testing neoadjuvant immunotherapies are needed to validate these findings and determine whether various immune cell populations may serve as biomarkers of therapeutic efficacy.…”
Section: Peripheral Immune Cellsmentioning
confidence: 99%
See 4 more Smart Citations
“…Peripheral densities of activated CD4 + T cells (CD69 + ) and NK cells (CD107a + ) were reduced post neoadjuvant therapy in patients who achieved pCR in resected tumors (78). Also, the authors found a decrease in the expression of PD-1 on peripheral CD4 + , CD8 + , and NK cells post neoadjuvant chemo-immunotherapy in patients who achieved pCR in resected tumors (78). Investigation of peripheral immunophenotyping in larger patient cohorts and across trials testing neoadjuvant immunotherapies are needed to validate these findings and determine whether various immune cell populations may serve as biomarkers of therapeutic efficacy.…”
Section: Peripheral Immune Cellsmentioning
confidence: 99%
“…Dynamic changes in peripheral immune cell populations following neoadjuvant immunotherapy and their association with tumor response to treatment are also being investigated in patients with resectable NSCLC for biomarker discovery. In these studies, blood samples were subjected to plasma-based cytokine arrays and analysis of PBMCs (peripheral blood mononuclear cells) by flow cytometry to identify the immunophenotypes of peripheral immune cells potentially associated with efficacy of ICIs (48,78). In the LCMC3 study (NCT02927301), blood samples were collected from patients pre-and posttreatment with neoadjuvant atezolizumab to investigate peripheral immunophenotyping and explore therapy-induced modulation of subsets of immune cell populations (48).…”
Section: Peripheral Immune Cellsmentioning
confidence: 99%
See 3 more Smart Citations